2022
DOI: 10.3390/ijms232113316
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Antimicrobial Peptide Spampcin56–86 from Scylla paramamosain Exerting Rapid Bactericidal and Anti-Biofilm Activity In Vitro and Anti-Infection In Vivo

Abstract: The abuse of antibiotics leads to the increase of bacterial resistance, which seriously threatens human health. Therefore, there is an urgent need to find effective alternatives to antibiotics, and antimicrobial peptides (AMPs) are the most promising antibacterial agents and have received extensive attention. In this study, a novel potential AMP was identified from the marine invertebrate Scylla paramamosain and named Spampcin. After bioinformatics analysis and AMP database prediction, four truncated peptides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Many AMPs have been demonstrated to directly target and disrupt bacterial membranes. Spampcin from Scylla paramamosain permeabilize S. aureus and P. aeruginosa outer and inner membranes [45]; A type I interferon (named gcIFN-20) from grass carp was shown to adsorb to the surface of S. aureus, and had a disrupting effect on the integrity of the bacterial cell membrane [28]. In the current study, localization of rPoHep2 and rPoNKL in bacteria were determined by indirect immunofluorescence.…”
Section: The Antibacterial Mechanism Of Rpohep2 and Rponklmentioning
confidence: 83%
“…Many AMPs have been demonstrated to directly target and disrupt bacterial membranes. Spampcin from Scylla paramamosain permeabilize S. aureus and P. aeruginosa outer and inner membranes [45]; A type I interferon (named gcIFN-20) from grass carp was shown to adsorb to the surface of S. aureus, and had a disrupting effect on the integrity of the bacterial cell membrane [28]. In the current study, localization of rPoHep2 and rPoNKL in bacteria were determined by indirect immunofluorescence.…”
Section: The Antibacterial Mechanism Of Rpohep2 and Rponklmentioning
confidence: 83%
“…However, the publication did not include in vitro or in vivo data [131]. Finally, Jiang et al used bioinformatics to generate four truncated AMPs of Spampcin (Spa31, Spa22, Spa20, and Spa14) [132]. Spa31 demonstrated potent antimicrobial activity against E. coli, P. aeruginosa, and S. aureus, inhibited/eradicated P. aeruginosa biofilms, and significantly improved the survival rate (from 50% to 79%) of Danio rerio zebrafish infected with P. aeruginosa [132].…”
Section: 'Novel' Amp Typesmentioning
confidence: 99%
“…Since 2006, our group has identified various novel AMPs in S. paramamosain , such as Scygonadin ( 7 ), Scyreprocin ( 8 ), Sparamosin 26–54 ( 9 ), Sparanegtin ( 10 ). and Spampcin 56–86 ( 11 ). In the present study, we identified a novel AMP named Scyampcin 44–63 from the mud crab S. paramamosain .…”
Section: Introductionmentioning
confidence: 99%